Gingival enlargement due to Amlodipine: Case report (Research, Society and Development, 2021)
Gingival enlargement is an increase in the size of the gum mostly caused by inflammatory changes associated with the prolonged accumulation of biofilm and induced by drugs, among which calcium channel blockers such as amlodipine stands out. Amlodipine is a 3rd generation drug, commonly used to treat conditions such as hypertension, arrhythmias and angina pectoris. The prevalence recorded for amlodipine-induced gingival enlargement, in patients with heart disease, ranges between 3%. Gingival enlargement induced by amlodipine is due to an interaction between gingival fibroblasts, the biochemistry of inflammation mediators and drug metabolites. The following is a case report of a 57-year-old man, hypertensive, with amlodipine-induced gingival enlargement, and with a diagnosis of periodontitis stage 3 grade C, who underwent basic periodontal therapy treatment and amlodipine was replaced by another antihypertensive drug, additionally for the final resolution of the case, a gingivectomy and open flap scaling and root planning in recurrent pockets was performed. It is concluded that the replacement of the drug induced gingival enlargement and adequate periodontal therapy can improve the patient’s gingival health and quality of life.